Une transition au féminin ? Modèles de parentalité et fécondité en Suisse (1955-1970) - Caroline Rusterholz; Anne-Françoise Praz (Genre, Sexualité et Société)
This article focuses on the role played by women in the transformation of sexual and family behaviors in two nearby Swiss cities between 1955-1970. This comparative study adopts the point of view of individuals and integrates a gender perspective. Based on 48 semi-structured interviews with elderly persons from the lower middle and working classes who were parents and married during the period under scrutiny, this paper asks how individuals conceived their parental roles, what were their knowledge and practices with regard to birth control. This paper sheds light on two developments, paradoxical at first glance, concerning the role of women in the baby bust. In contrast with the idea of modernization and emancipation from traditional norms, the model of the mother as a housewife was more important than ever in this period. However, women were proactive in the field of contraception. Thus, it was not through female emancipation that women widened their field of expertise to sexuality but rather paradoxically through their individual adhesion to the traditional model of the mother as a housewife available and skilled for her children.